Exponential decay for a strain gradient porous thermoelasticity with second sound - Ahmima, Afaf; Fareh, Abdelfeteh (Armenian Journal of Mathematics, 2022)
In this paper, we consider a strain gradient porous elastic bar subjected to a thermal disturbance modelled by Cattaneo's law for heat conduction. We use the semigroup approach to prove the existence of a unique weak solution. Although the thermal dissipation induced by the second sound thermoelasticity is weaker than that caused by the classical heat conduction, we prove that the solution decays exponentially.
Keywords: strain gradient; thermoelasticity; second sound; exponential decay